Sport related performance anxiety in collegiate student athletes: examining the effects of COVID-19 - Hogan, G. (2022)
This study uses a combination of survey instruments and qualitative measures to analyze and seek to understand levels of performance anxiety in division 3 student athletes and how the Covid-19 pandemic has impacted this.